Biomechanical effects of individualized artificial titanium alloy lamina implantation after laminectomy: A finite element analysis - Gong, Xuqiang; Zhang, Aobo; Han, Qing; Wang, Yang; Liu, Yang; Jiao, Jianhang; Yue, Jing; Chen, Hao; Luo, Wangwang; Wang, Jincheng; Wu, Minfei (Frontiers in Bioengineering and Biotechnology, 2022)
Background and objectives: Laminectomy is a common surgical procedure in spine surgery. However, disruption of the posterior ligamentous complex of the spine may lead to a range of postoperative complications. Artificial lamina as a kind of bionic implant can well restore the posterior spinal structure. In this study, an individualized artificial titanium alloy lamina was designed to reconstruct the posterior spinal structure after laminectomy and explored its biomechanical effects, which could provide a theoretical basis for the clinical application of the artificial lamina. Methods: Three finite element models were constructed, namely the nonlinear and non-homogeneous intact model of the whole lumbar spine, the lumbar decompression alone surgical model, and the artificial lamina implantation surgical model. The range of motion, intradiscal pressure, and annulus fibrosus peak stress were compared between the three models at the surgical and adjacent segments. The stresses of the artificial lamina and fixation screws were also analyzed for the four movement states. Results: Compared with the intact model, the lumbar decompression alone surgical model showed an increase in range of motion, intradiscal pressure, and annulus fibrosus peak stresses at the surgical segment and adjacent segments under all conditions. The artificial lamina implantation surgical model showed an increase in these measurements only in flexion, increasing by 7.5%-22.5%, 7.6%-17.9%, and 6.4%-19.3%, respectively, over the intact model, while there was little difference under other conditions. The peak stresses in both the screw and the artificial lamina were highest in axial rotation, i. e. 46.53 MPa and 53.84 MPa, respectively. Screw stresses were concentrated on the connection between the screw and the artificial lamina, and artificial lamina stresses were concentrated on the spinous root, around the screw hole, and the contact with the vertebral body. Conclusions: An individualized artificial titanium alloy lamina can effectively reduce the range of motion, intradiscal pressure, and annulus fibrosus stress at the surgical segment and adjacent segments. The application of artificial lamina could better preserve the biomechanical properties of the intact lumbar spine and reduce the incidence of failed back surgery syndrome as well as adjacent segmental disease, which improves the living quality of patients.